Struktura arki Noego (Rdz 6,14-16) w łacińskich źródłach patrystycznych przed Augustynem z Hippony - Kochanek, Piotr (Vox Patrum, 2024)
The article analyzes the comments of eleven Latin authors on the structure of Noah’s Ark (Genesis 6:14-16). These authors are: Tertullian, Cyprian, Pseudo-Cyprian, Victorinus of Patavia, Lactantius, Hilary of Poitiers, Gregory of Elvira, Ambrose of Milan, Maximus of Turin, Jerome of Strydon and Orosius. The most important points in their analyzes of the flood pericope were three typologies: Noah – Christ, Noah’s ark – the Church of Christ, the waters of the flood – the water of baptism. These typologies were closely related to the thesis regarding the exclusivity of salvation in the Church. The structure of the ark was a secondary or even tertiary problem in this context. However, over time, interest in this issue also gained attention. Gregory of Elvira and Ambrose of Milan paid the most attention to the „technical” structure of the Ark. A translation of Origen’s Second Homily on the Book of Genesis by Rufinus of Aquileia should be added here. These writers drew attention to the pyramidal shape of Noah’s Ark and the two-stage division of its interior: storeys and floors. The symbolic meaning of the dimensions of the Ark was also analyzed. The Ark-Church typology has also been linked to considerations on the Church as the mystical body of Christ. In this way, Latin theologians, even before the translation of Origen’s homily by Rufinus, either adopted the ideas of the Greek Fathers of the Church or reached the same conclusions themselves.